2017
DOI: 10.17795/mejrh-37043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dental Status and Its Association with Oral Health-Related Quality of Life in Preschool Children in Zahedan City, Iran: A Cross-Sectional Study

Abstract: Background: Several factors can affect the oral health-related quality of life in children. Objectives: The aim of this study was to evaluate the dental status and its relationship with the oral health-related quality of life in preschool children in Zahedan City, Iran. Methods: In this descriptive-analytical cross-sectional study, 200 preschool children (5 -6 years old) were randomly selected from different areas of Zahedan city. Dental health status of children was investigated using the decayed, missing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
(20 reference statements)
2
11
1
Order By: Relevance
“…In the present study, the mean score of oral healthrelated quality of life was 11.88 ± 6.91 in preschool children of Gorgan, which is in agreement with a study by Amirabadi et al [21] in preschool children of Zahedan (10.94 ± 7.69) and another study in preschool children of Babol (6.65 ± 3.57) [22]. Moreover, the results of a study by Sajjadi et al in Kerman preschool children [23] showed that the ECOHIS score was 4.07 ± 0.79 for children and 3.28 ± 0.83 for their parents.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the mean score of oral healthrelated quality of life was 11.88 ± 6.91 in preschool children of Gorgan, which is in agreement with a study by Amirabadi et al [21] in preschool children of Zahedan (10.94 ± 7.69) and another study in preschool children of Babol (6.65 ± 3.57) [22]. Moreover, the results of a study by Sajjadi et al in Kerman preschool children [23] showed that the ECOHIS score was 4.07 ± 0.79 for children and 3.28 ± 0.83 for their parents.…”
Section: Discussionsupporting
confidence: 93%
“…The dmft score does not consider the stages of progression of carious lesions, for example early lesion or deep severe carious lesion were charted as decayed teeth only. Therefore, the use of a more precise charting techniques such as the ICDAS II or the Pulpal involvement, Ulceration due to trauma, Fistula and Abscess (PUFA/pufa) index for the detection of carious lesions may provide better clinical information in the investigation of OHRQoL in children [36,37].…”
Section: Family Impactmentioning
confidence: 99%
“…Meanwhile, Gonabad and Bajestan are two desert cities locating in Eastern part of Iran. The results of some studies in similar climate zones in Iran show a high DMFT index in these areas (15), although other studies in tropical and desert regions have reported different results (22,23). So, according to the above mentioned issues as well as the importance of regional studies to recognize the oral health status and, if necessary, design and implement intervention programs appropriate to the regional conditions, this study aims to examine the DMFT in 12-year-old students of Gonabad and Bajestan and determine some of their affecting factors.…”
Section: Introductionmentioning
confidence: 92%
“…Various studies have found that many factors such as Socio-Economic Status (SES), parents' education level and occupation, sex, and birth rank would affect the children's oral health status (9,14). There are also some studies that, in desert areas, show the DMFT among children is roughly high (15)(16)(17)(18)(19); Therefore, since Iran is still considered as a young country (20), planning and implementing to prevent and treat oral diseases would be necessary.…”
Section: Introductionmentioning
confidence: 99%